2020
DOI: 10.1002/alz.12090
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and risk of Alzheimer's disease: Small association in a nationwide cohort study

Abstract: INTRODUCTION:Small observational studies with short-term follow-up suggest cancer patients are at reduced risk of Alzheimer's disease (AD) compared to the general population.METHODS: Nationwide cohort study using Danish population-based health registries with cancer patients (n=949,309) to identify incident diagnoses of AD. We computed absolute reductions in risk attributed to cancer and standardized incidence rate ratios (SIRs) accounting for survival time, comparing observed to expected number of AD cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
(75 reference statements)
1
29
0
Order By: Relevance
“…Our search returned 2764 unique records; 22 studies (19 cohort studies and 3 case-control studies) met the eligibility criteria and were included (eFigure 1 in the Supplement ). In total, 13 studies 10 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 investigated all cancer types (eTable 2 in the Supplement ); 5 studies 49 , 50 , 51 , 52 , 53 investigated prostate cancer; 3 studies 9 , 54 , 55 investigated NMSC; and 1 study 56 investigated breast cancer ( Table 1 ). Five studies that investigated all cancer types (5 of 13) additionally reported cancer type–specific subgroup analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Our search returned 2764 unique records; 22 studies (19 cohort studies and 3 case-control studies) met the eligibility criteria and were included (eFigure 1 in the Supplement ). In total, 13 studies 10 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 investigated all cancer types (eTable 2 in the Supplement ); 5 studies 49 , 50 , 51 , 52 , 53 investigated prostate cancer; 3 studies 9 , 54 , 55 investigated NMSC; and 1 study 56 investigated breast cancer ( Table 1 ). Five studies that investigated all cancer types (5 of 13) additionally reported cancer type–specific subgroup analyses.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Although some recent studies report smaller effect estimates, meta-analyses show that dementia incidence is 15% to 38% lower among those with history of cancer compared to those without. 1,[3][4][5][6][7]37 Some studies examining diverse site-specific cancers,…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial literature on the inverse cancer‐dementia association 1–10 . Although some recent studies report smaller effect estimates, meta‐analyses show that dementia incidence is 15% to 38% lower among those with history of cancer compared to those without 1,3‐7,37 . Some studies examining diverse site‐specific cancers, including breast, colorectal, lung, and non‐melanoma skin cancers, show similar results 1,8,9,11,12 .…”
Section: Discussionmentioning
confidence: 99%
“…However, contrary to general expectations, patients with cancer in some of these analyses demonstrated a decreased risk of dementia (summarized, e.g., in [ 4 ]). Other analyses reported that these inverse correlations between cancer and dementia might be restricted to specific etiologies such as Alzheimer’s disease and diminish over time, arguing that the association between cancer and general risk of dementia is limited [ 12 ]. Furthermore, other authors reported a positive association between tumor markers and dementia rates in cancer patients [ 13 ].…”
Section: Introductionmentioning
confidence: 99%